BATTLES IN BRITAIN AND THEIR POLITICAL BACKGROUND, 1066-1746 - Van der Waag, Ian (Scientia Militaria - South African Journal of Military Studies, 2012)
William Seymour has produced the field guide to British battlefields for which military historians and battlefield tramplers have been waiting. Battles in Britain is a detailed account of thirty-two major battles fought on British soil from the Norse invasion under King Harold Hardrada (September 1066) through to the second Jacobite insurrection (1746). Every campaign, battle or action is skilfully analysed and the combat circumstances of each case are vividly recreated. Special attention is given to strategy, tactics and the principles of war - the professed focus of the book. The discussion is in most instances familiar: the use of interior lines by Harold Godwinson in 1066 and again by the Roundheads during the English Civil War; the successful usage of a Fabian strategy by the Scots in their wars against the English, and their often suffering defeat when pursuing a combat strategy. While most similar works stop here, Seymour goes further. He not only attempts to describe the emotions of the men (fear, boredom, weariness, despair, defiance and exhilaration), but also sets each battle against the political and historical background of the time. Seymour addresses not only the causes for each of the wars, but also the justness of each protagonist’s resort to arms. This provision of context, and of the backdrop against which the campaigns and battles took place, is essential.